Immunogenic Response of Brucella canisvirB10 and virB11 Mutants in a Murine Model - Palomares, Gabriela; Arellano, Beatriz; Hernandez, Rigoberto; Tenorio, Victor; Salas, Enrique; Suarez, Francisco; Diaz, Efrén (Frontiers in Cellular and Infection Microbiology, 2012)
The virB locus, which encodes for the type IV secretion system, is a major component of virulence in Brucella. A non-polar virB10 mutant and virB11 deletion mutant were constructed in Brucella canis. In the mouse model both mutants were cleared at day 21 p.i., indicating reduced virulence in mice. After the challenge with a wild type B. canis the amount of CFU recovered at 15 day was significantly lower in the group previously vaccinated with virB10 mutant. Levels of IgG1, IgG2a, IgG2b and IgM as well as the induction of cytokines IL-2, IL-4, IL-10 and IFN- production, were measured in lymphocyte cultures. All strains elicited similar levels of different antibody isotype profiles, no significant difference was detected (P<0.05). The wild type induced a rapid and strong response of INF-γ at 24 h, while both mutants induced a mild response of INF-γ at 24 h, which remained constant during all sampling.